Friction Coefficient and Wear Rate of Copper and Aluminum Sliding against Mild Steel - Nuruzzaman, D. M.; Chowdhury, M. A. (TuEngr Group, 2012)
In this research, friction and wear of copper and aluminum are investigated experimentally using a pin-on-disc apparatus. In the experiments, mild steel pin slides on copper or aluminum disc at different normal load conditions 10, 15, and 20 N. Experiments are also carried out at different sliding velocities 1, 1.5 and 2 m/s. The effects of duration of rubbing on the friction coefficient of copper and aluminum are investigated. It is found that during friction process, copper or aluminum disc takes less time to stabilize as the normal load or sliding velocity increases. Time to reach steady friction varies depending on applied normal load or sliding velocity for both copper and aluminum. Within the observed range, friction coefficient decreases when applied load is increased while it increases when sliding velocity is increased for both copper and aluminum. In general, wear rate increases with the increased normal load and sliding velocity. Finally, as a comparison, it is found that friction coefficient and wear rate of copper are much lower than that of aluminum within the observed range of normal load and sliding velocity.